Admittance of a one-dimensional double-barrier resonant tunneling nanostructure - Shangguan, Wang Zuo (2018)
We study the dynamic response of a one-dimensional double-barrier nanostructure to an ac bias. Combining the Schrödinger equation, Poisson equation and the scattering theory, we calculate the internal potential, charge density, and the ac conductance as well. The results show that the charge distribution is antisymmetric with respect to the center of the double barrier, and depends crucially on the relative position of the Fermi level to the resonant energies of the well. The diagonal emittance is found to have a similar dependence. It is negative (inductive behavior) when the Fermi energy is very close to the resonant energies, and it reaches the negative maximum at resonant energies, while it is always positive (capacitive behavior) when the Fermi energy is within the barrier depth and far from resonance, and develops two peaks closely on both sides of the inductive peak. This result is in agreement with that obtained from discrete model. In addition, we find that the capacitive peaks correspond to the maxima of charge-density fluctuation, and inductive peaks to zero charge-density distribution. Therefore, the sign and magnitude of emittance reflect how the charge piles up inside the device.